The unbearable divergence of unemployment in Europe - Boeri, Tito; Jimeno Serrano, Juan Francisco (London, 2015)
"Unemployment in Europe is not only “too high”, it is also too different across countries that belong to a monetary union. In this paper we i) document this increasing heterogeneity, ii) try to explain it and iii) draw from our diagnosis indications as to the appropriate set of policies to reduce unemployment and labour market disparities. Our analysis suggests that the divergence in labour market outcomes across Europe is the by-product of interactions between, on the one hand, shocks of varying size and nature, and, on the other hand, country-specific labour market institutions. We argue that EU policy coordination and conditionality during the Great Recession and the euro area debt crisis did not properly take into account these interactions. We also propose a change in the European policy approach for fighting unemployment."